2017
DOI: 10.1021/acs.energyfuels.7b02771
|View full text |Cite
|
Sign up to set email alerts
|

Drying of Thermally Thick Wood Particles: A Study of the Numerical Efficiency, Accuracy, and Stability of Common Drying Models

Abstract: The primary focus of this paper is on studying dierent numerical models for drying of wet wood. More specically, the advantages and disadvantages of the models with respect to numerical eciency, stability and accuracy are investigated. The two basic models that are studied in detail are the thermal drying model and the kinetic rate drying model. The drying models have been implemented in an in-house simulation tool that solves for drying and devolatilization of a one-dimensional cylindrical wood log.It is foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(40 citation statements)
references
References 37 publications
2
38
0
Order By: Relevance
“…The kinetic model assumes a first-order Arrhenius reaction of the liquid water phase turning into vapour. In work by Haberle et al [64] a summary of the commonly used parameters for this model can be found. The kinetic model is very convenient, but it treats a physical phenomenon via a chemical description, so it does not reflect the process well in real terms.…”
Section: Kinetic Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The kinetic model assumes a first-order Arrhenius reaction of the liquid water phase turning into vapour. In work by Haberle et al [64] a summary of the commonly used parameters for this model can be found. The kinetic model is very convenient, but it treats a physical phenomenon via a chemical description, so it does not reflect the process well in real terms.…”
Section: Kinetic Modelmentioning
confidence: 99%
“…The heat sink model (thermal drying model, heat flux model) [57,64,65] assumes that water evaporation in a representative volume occurs only at the boiling temperature, and the temperature stays constant until all water is evaporated. To maintain a constant temperature, the evaporation reaction needs to consume all the energy transferred to the representative volume.…”
Section: Heat Sink Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The presented equations only consider the devolatilization stage, since in the current test run, drying and char conversion are not modeled. Further details on the model development can be found in earlier works by Haberle et al [11,12]. Table 1.…”
Section: Wood Log Modelmentioning
confidence: 99%